2010
DOI: 10.1260/1369-4332.13.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Field Investigation on Dynamics of Railway Track Pre-Stressed Concrete Sleepers

Abstract: A comprehensive field investigation was made with the aim of achieving a better understanding of the dynamics of railway track pre-stressed concrete sleepers. Modal analysis and free decay method were used to determine the natural frequencies, model shapes and damping of sleepers. The validity of the results is discussed by comparing the results obtained here with those available in the literature. In order to investigate the characteristics of the dynamics of the loads imposed on the sleepers, load cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Therefore, the use of the AREMA recommendation (Table 1) for dynamic impact factor is suggested for heavy haul railway with the train speed less than 80 km/h. On the other hand, the use of mathematical expression proposed by ORE (indicated in Table 1) is more justifiable for the calculation of dynamic impact factor in high speed railway tracks [31]. The effects of the dynamic characteristics of the load on the sleeper and the ballast (Rail-seat load and ballast-sleeper contact pressure) have been recently investigated by Sadeghi and his colleagues [31].…”
Section: Dynamic Impact Factor (Dif)mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the use of the AREMA recommendation (Table 1) for dynamic impact factor is suggested for heavy haul railway with the train speed less than 80 km/h. On the other hand, the use of mathematical expression proposed by ORE (indicated in Table 1) is more justifiable for the calculation of dynamic impact factor in high speed railway tracks [31]. The effects of the dynamic characteristics of the load on the sleeper and the ballast (Rail-seat load and ballast-sleeper contact pressure) have been recently investigated by Sadeghi and his colleagues [31].…”
Section: Dynamic Impact Factor (Dif)mentioning
confidence: 99%
“…On the other hand, the use of mathematical expression proposed by ORE (indicated in Table 1) is more justifiable for the calculation of dynamic impact factor in high speed railway tracks [31]. The effects of the dynamic characteristics of the load on the sleeper and the ballast (Rail-seat load and ballast-sleeper contact pressure) have been recently investigated by Sadeghi and his colleagues [31]. They indicated that the dynamic characteristics of the load have more impact on the amount of ballast-sleeper pressure at the points which experience less pressure.…”
Section: Dynamic Impact Factor (Dif)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the need for sleepers' replacement in old railroads has been increasing, as well as the average increase of the speed guide provided by increasingly modern trains, which economically justifies the large amount of studies on this theme around the world [5,12,13].The sleepers are subjected to cyclic loads during their whole life; the materials that comprise them are subjected to an intense process of fatigue. It is desirable that the sleeper is free of cracks under dynamic loading, because if cracks occur, there is a great increase in stresses in the prestressing reinforcement and an increase of up to 50% in the transfer length [14][15][16]. Therefore, designing a prestressed sleeper is a good solution to avoid problems with simple concrete [1,15,17,18].Thus, this paper aims to evaluate the mechanical behavior of prestressed concrete sleepers, in accordance with the Brazilian and American standards and the common pathologies they are submitted to over their design life.…”
mentioning
confidence: 99%